Detection of Marker-Free Precision Genome Editing and Genetic Variation through the Capture of Genomic Signatures - Billon, Pierre (Cell Rep, 2020)
Genome editing technologies have transformed our ability to engineer desired genomic changes within living systems. However, detecting precise genomic modifications often requires sophisticated, expensive, and time-consuming experimental approaches. Here, we describe DTECT (Dinucleotide signaTurE CapTure), a rapid and versatile detection method that relies on the capture of targeted dinucleotide signatures resulting from the digestion of genomic DNA amplicons by the type IIS restriction enzyme AcuI. DTECT enables the accurate quantification of marker-free precision genome editing events introduced by CRISPR-dependent homology-directed repair, base editing, or prime editing in various biological systems, such as mammalian cell lines, organoids, and tissues. Furthermore, DTECT allows the identification of oncogenic mutations in cancer mouse models, patient-derived xenografts, and human cancer patient samples. The ease, speed, and cost efficiency by which DTECT identifies genomic signatures should facilitate the generation of marker-free cellular and animal models of human disease and expedite the detection of human pathogenic variants.